The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/modpathol.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Are the uterine serous carcinomas underdiagnosed? Histomorphologic and immunohistochemical correlates and clinical follow up in high-grade endometrial carcinomas initially diagnosed as high-grade endometrioid carcinoma

Abstract: Histologic subclassification of high-grade endometrial carcinomas can sometimes be a diagnostic challenge when based on histomorphology alone. Here we utilized immunohistochemical markers to determine the immunophenotype in histologically ambiguous high-grade endometrial carcinomas that were initially diagnosed as pure or mixed high-grade endometrioid carcinoma, aiming to determine the utility of selected immunohistochemical panel in accurate classification of these distinct tumor types, while correlating thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…The application of biomarkers (i.e., immunohistochemical staining) assists pathologists in rendering more accurate diagnoses. A recent study found that up to 40% of cases initially diagnosed as high-grade endometrial endometrioid adenocarcinomas may be reclassified as uterine serous carcinomas based on a panel of four immunostains (p53, p16, estrogen receptor (ER), and mammaglobin) [ 10 ]. Immunostains in routine practice, however, are often not pursued due to a pathologist's degree of morphologic certainty or the possibility of ambiguous results.…”
Section: Introductionmentioning
confidence: 99%
“…The application of biomarkers (i.e., immunohistochemical staining) assists pathologists in rendering more accurate diagnoses. A recent study found that up to 40% of cases initially diagnosed as high-grade endometrial endometrioid adenocarcinomas may be reclassified as uterine serous carcinomas based on a panel of four immunostains (p53, p16, estrogen receptor (ER), and mammaglobin) [ 10 ]. Immunostains in routine practice, however, are often not pursued due to a pathologist's degree of morphologic certainty or the possibility of ambiguous results.…”
Section: Introductionmentioning
confidence: 99%
“…Assignment to the appropriate grade is based on the percentage of solid non-squamous, non-morular tumor cells during histopathological evaluation, with grade 3 assigned to cases with over 50% of the tumor cells. However, this assignment is affected by the inter-observer variability, especially in high-grade EC, when the diagnosis is based on histomorphology alone [5,6]. The availability of molecular methods encourages to support EC diagnosis with genomic and transcriptomic data.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike EEC, USC tends to develop in elderly women, with low body weight and arises in the background of atrophic endometrium (4). Microscopically, USC typically forms complex papillary structure with almost high-grade polymorphic nuclei in contrast to glandular/cribriform pattern with mild to moderate atypical nuclei in EEC (5,6). 80-90% of USC tumors harbor TP53 mutation while retaining wildtype PTEN but losing ER/PR expression (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, USC typically forms complex papillary structure with almost high-grade polymorphic nuclei in contrast to glandular/cribriform pattern with mild to moderate atypical nuclei in EEC (5,6). 80-90% of USC tumors harbor TP53 mutation while retaining wildtype PTEN but losing ER/PR expression (5)(6)(7)(8). USC accounts for almost 10% of endometrial cancers but is disproportionately responsible for poor outcomes, contributing up to 40% cancer-related deaths from endometrial cancer (4).…”
Section: Introductionmentioning
confidence: 99%